Interaction of Russia and the Russian Orthodox Church with Christian communities in Egypt and Ethiopia in the second half of the 19th — early 20th century - V. Michael Nigusie Kassae; N. N. Morozova (Российский журнал истории Церкви, 2022)
The article presents the history of the relationship of the Russian Orthodox Church with the Christian communities of Egypt and Ethiopia. The article is also concerned with the issue of contacts between the Russian Orthodox Church and the Coptic Church of Egypt in the second half of the 19th and early 20th century. The first almost informal contacts between representatives of the Russian Orthodox Church and the Alexandria Patriarchate allowed Egyptian Christians to get acquainted with the activities of the Russian Orthodox Church, and representatives of the Russian Orthodox Church — with the real state of the religious, political and cultural situation in Egypt. The article also examines the attempts of representatives of the Russian Orthodox Church to establish ties with the Ethiopian Orthodox Church, which was part of the Alexandria Patriarchate until 1959.